Factors Affecting Taxpayer Compliance of E-commerce in West Java - Shafaa Sekar Pembayun Ananureko; Pratiwi, Selviani (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of this study is to look into the aspects that can influence taxpayer compliance among e-commerce business players, such as knowledge of tax regulations, taxpayer awareness, e-filing use, and tax sanctions. This research method employs a quantitative approach to the data used, specifically primary data. The primary data was collected via delivering questionnaires to respondents. This study employed multiple linear analysis with IBM SPSS Statistics software version 25. This study's population consists of taxpayers from e-commerce company players in West Java, with a sample size of 100. The findings revealed that understanding of tax regulations, taxpayer awareness, and tax sanctions all had a considerable favorable impact on taxpayer compliance. However, the usage of e-filing demonstrates that it has no substantial influence on taxpayer compliance. And the findings of this study are intended to be used by connected parties to continue organizing socialization about the need of paying taxes among business actors in e-commerce.